Quantitative Trait Locus Mapping of Flowering Time and Maturity in Soybean Using Next-Generation Sequencing-Based Analysis - Kong, Lingping; Lu, Sijia; Wang, Yanping; Fang, Chao; Wang, Feifei; Nan, Haiyang; Su, Tong; Li, Shichen; Zhang, Fengge; Li, Xiaoming; Zhao, Xiaohui; Yuan, Xiaohui; et al. (Frontiers in Plant Science, 2018)
Soybean (Glycine max L.) is a major legume crop originating in temperate regions. The adaptability of soybean to be grown at a relative high latitudes is attributed to natural variation in the major genes and QTLs that control flowering time and maturity. Identification of new QTLs and map-based cloning of the candidate genes are the fundamental approaches to understand the mechanism of soybean flowering and adaptation. To identify novel QTLs/genes, we developed two F8:10 recombinant inbred lines (RILs) and evaluated time to flowering (R1), maturity (R8) and reproductive period (RP) traits in the field. To fast and efficiently identify QTLs control these traits, we carried out NGS-based QTL analysis. Our results demonstrated that only one major QTL simultaneously controlling R1, R8 and RP traits was detected on Chromosome 04 in Dongnong 50×Williams 82 (DW) RIL population. While Four QTLs were mapped on Chromosome 06, 11, 16 and 19 in Suinong 14×Enrei (SE) RIL population. QTLs on Chromosome 04 and 06 were two major pleiotropic QTLs affect not only flowering time but also reproductive period. QTL on Chromosome 11 mainly affected reproductive period, while QTLs on Chromosome 16 and 19 mainly affected time to flowering responses. All these QTLs worked together to contribute the whole length of maturity in soybean. The QTLs identified here could be useful for understanding of genetic diversity in controlling flowering and post-flowering responses. Further fine mapping and map-based cloning of the candidate genes could be critical to understand the flowering mechanism and soybean adaptation and to breed new soybean cultivars for optimization of yield traits and adaptation capacity to high latitude.